Possible effect of climate change on the potential distribution of temperate forest tree species in Nuevo León, Mexico - Manzanilla-Quijada, Gyorgy Eduardo; Treviño-Garza, Eduardo Javier (Ecosistemas y Recursos Agropecuarios, 2024)
The global climate is changing significantly in recent years and with it the distribution of some species. The objective of this study was to estimate the impact of climate change on the potential distribution of 10 temperate forest tree species in the state of Nuevo León, Mexico, and to define conservation areas. The current and future potential distribution of each species was estimated from records and environmental variables, using 75% of the records to train and 25% to validate the models in the MaxEnt algorithm. The occupied surface of the study area was calculated and the percentage of reductions and increases under two scenarios (RCP4.5 and RCP8.5) of climate change was obtained. The results show AUC values above 0.900 for the training and validation data, however, the partial ROC tests showed values above 1.700, while the Z-analyses indicated excellent statistical performance (p<0.01). Of the 10 species, four will experience reductions in their ranges, with A. vejarii 8690 ha, P. pseudostrobus 6852 ha, P. teocote 4197 ha and Q. polymorpha 10828 ha in 2050. The variables with the greatest contribution were Bio8, Bio7, Bio6 and Bio19, so that the modification of any of these variables would mean a considerable reduction in their populations and could even cause some local extinctions. Based on the results obtained, decisions could be made and management measures could be implemented for the conservation of certain species.